A internacionalidade da arbitragem à luz do Direito Brasileiro - Zanelato, Thiago Del Pozzo (2020)
The present work aims to verify if Brazilian Law recognizes international arbitration as an autonomous institute and, if so, whether it elects (or accepts) criterion(criteria) of internationality to identify an arbitration as international. In order to establish the foundations of the institute of arbitration, some concepts and fundamental notions will be analyzed in order to outline the historical origin and the evolution of arbitration, its legal nature and varieties usually verified. In the aftermath, the examination of internationality within the scope of arbitration is made: its relation with Private International Law, the relevance of the discussion as a distinctive criterion of international arbitration, the principles that govern international arbitration, its legal foundations, the monist and dualist arbitration systems, the criteria for identifying internationality and the relationship between foreign arbitral award and the internationality of arbitration. In Brazil’s framework, the analysis brings a historical overview of the development of Brazilian legislation on the subject until the enactment of the Brazilian Arbitration Act, with specific considerations about the importance of international conventions that have been ratified in Brazil for the formation of the basis of the Brazilian arbitration system. Once the premises of the international arbitration system that is in force in Brazil and the applicable criteria for the assessment of the internationality of arbitration have been established, the last part of this work analysis the reasons and practical consequences which indicate the need to distinguish domestic arbitration from international arbitration in Brazil. The conclusion presents a proposal of systematization involving the current international arbitration system existing in Brazil and its consequences